Application of glycerol as carbon source for continuous drinking water denitrification using microorganism from natural biomass - Schroeder A.* (2020)
© 2019 Elsevier LtdThe contamination of water resources by nitrate is a global problem. Indeed, traditional treatment technologies are not able to remove this ion from water. Alternatively, biological denitrification is a useful technique for natural water nitrate removal. This study aimed to evaluate the use of glycerol as a carbon source for drinking water nitrate removal via denitrification in a reactor using microorganisms from natural biomass. The experiment was carried out in a continuous fixed bed reactor using immobilised microorganisms from the vegetal Phyllostachys aurea. The tests were started in batch mode to provide cells growth and further immobilisation on the support. Then, the treatment experiments were accomplished in an up-flow continuous reactor. Ethanol was used as the primary carbon source, and it was gradually replaced by glycerol. The C:N (carbon to nitrogen) ratio and the hydraulic residence time (HRT) were evaluated. It was possible to remove 98.14% of nitrate using a C:N ratio and HRT of 3:1 and 1.51 days, respectively. The results have demonstrated that glycerol is a potential carbon source for denitrification in a continuous reactor using immobilised cells from natural biomass.